Comparison of Trust Assessment Scales Based on Item Response Theory - Dai, Buyun; Zhang, Wenqing; Wang, Yang; Jian, Xiaozhu (Frontiers in Psychology, 2020)
Three widely used interpersonal trust measurement scales [Interpersonal Trust Scale (ITS), Philosophies of Human Nature Scale (RPHNS), Company Trust Scale (CTS)] have seldom been applied in non-Western contexts. Different social environments may lead to variation in the level or structure of trust. Therefore, it is necessary to compare the applicability of these scales to different levels of trust-related traits in Eastern cultures so that researchers can choose appropriate scales for relevant studies. This study attempted to conduct a comparative analysis of the ITS, RPHNS, and CTS. A sample of 725 Chinese college students was analyzed. Total score correlations and latent factor correlations estimated by confirmatory factor analysis (CFA) for a first-order three-factor model were assessed, and then the quality of the item parameters, test reliability and standard errors, and test information were assessed. The results are as follows: (1) the ITS and the RPHNS assessed almost the same trust traits; therefore, only the ITS and the RPHNS are compared in the next sections; (2) the original structure of only the RPHNS is verified; (3) some items on the ITS do not work well, while the RPHNS has higher overall test reliability; and (4) the average item information provided by the RPHNS is higher across all trait levels. In most cases, the RPHNS is the better choice in the Chinese cultural context.